Pengaruh Poster Pencegahan Anemia Terhadap Perilaku Dan Kadar HB Ibu Hamil di Wilayah Kerja Puskesmas Baki Sukoharjo - Arwin, Arminiati; , Sulastri, S.Kp.,M.Kes (2017)
Introduction Poster is a short message in the form of images with the aim of influencing someone to be interested and act on something. Awareness of pregnant women is necessary for the prevention of anemia. Knowledge is the first step of behavior change, then it is important to provide information about anemia to pregnant women through the medium of learning. The purpose of this study was to determine whether there is a poster effect on behavior and maternal hemoglobin concentration. Research method is Pre experimental research design with one group pretest posttest. This research was conducted in the area of the health center Sukoharjo Baki in January 2017 with a sample of 30 pregnant women trimester I-III and purposive sampling technique. The instrument used was a questionnaire prevention of anemia and hemoglobin measurement device Easy Touch. Test to determine the parametric test data analysis using paired t test. The results showed when installed anemia prevention posters change negative behavior into positive behavior of respondents with a significance of 0.000. Likewise with Hb where there are differences in Hb levels were previously the majority of respondents had mild anemia to be normal with a significance value of 0.005. Both variables have a significance value of p <0.005. Limitations of the study is collecting data to measure the behavior of researchers used the instrument of accession with the Likert scale questionnaire research when data collection to better measure the behavior is by observation. For 30 days the researchers did not monitor every day about the consumption of nutritious food, the cleanliness of the home environment, the consumption of iron tablet and pregnancy testing. Researchers also do not provide bahanseperti green vegetables, orange juice were both taken together with iron tablet etc so not all pregnant women can increase levels of Hbnya probably due to lack of food that is good for preventing anemia. The conclusion shows the influence of anemia prevention posters on behavior and maternal hemoglobin concentration in Puskesmas Baki, Sukoharjo. Suggestions for health centers by adding a poster that contains health information on the prevention of anemia and health education programs on a regular basis in the mother can improve the quality of health services in health centers and education institutions are expected to improve and add to the literature on pnelitian a deeper understanding of the prevention of anemia in pregnant women.